The effect of ultrasound-guided thoracic paravertebral nerve block combined with hydromorphone on postoperative analgesia and inflammatory response in thoracoscopic surgery: a randomized controlled trial - Zeng, Lin; Yu, Xiaoxue; Yang, Ting; Liao, Jing; Ouyang, Yinghui (Frontiers in Medicine, 2025)
ObjectiveThis study aims to explore the effects of a multimodal postoperative analgesia regimen of ultrasound-guided thoracic paravertebral block (UTPB) combined with hydromorphone patient-controlled intravenous analgesia (PCIA) on postoperative analgesia, early recovery, and traumatic inflammatory response in patients undergoing thoracoscopy surgery, providing a basis for clinical application.MethodsIn this single-blind, randomized controlled trial (RCT), we enrolled 64 patients scheduled for thoracoscopic lobectomy of the lung. The patients were randomly assigned into two groups of UTPB combined with hydromorphone PCIA group (T group) and hydromorphone PCIA group (H group) according to the random number table method. T group underwent UTPB with ropivacaine before induction of general anesthesia. H group is the control group. Both groups underwent PCIA after surgery, with the analgesic formula being 50 μg/kg of hydromorphone. The analgesic solution is prepared with 100 mL of sodium chloride injection, a background dose of 2.0 mL/h, a patient-controlled analgesia dose of 2 mL, and a locking time of 30 min.ResultsCompared with H group, T group showed a significant decrease in visual analog scale (VAS) scores and an increase in bruggrmann comfort scale (BCS) scores within 8 h after surgery, and a decrease in opioid analgesic doses during and within 8 h after surgery. The levels of serum C-reactive protein (CRP), Interleukin-6 (IL-6), and tumor necrosis factor (TNF-α) in T group were lower than those in H group at 24 h after surgery. The first time patients in T group got out of bed after surgery was earlier than that in H group. Two groups of patients had no serious adverse reactions.ConclusionUltrasound-guided thoracic paravertebral block combined with hydromorphone PCIA can achieve good analgesic effects in thoracoscopic lobectomy surgery. It can reduce the amount of opioid drugs used during the perioperative period, alleviate the body’s inflammatory response, and promote rapid recovery of patients. It has clinical application value.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=201650, identifier ChiCTR2300074082.